If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 4y + 5) + 2(2x + -4y + -3) = 0 Reorder the terms: 3(5 + 3x + 4y) + 2(2x + -4y + -3) = 0 (5 * 3 + 3x * 3 + 4y * 3) + 2(2x + -4y + -3) = 0 (15 + 9x + 12y) + 2(2x + -4y + -3) = 0 Reorder the terms: 15 + 9x + 12y + 2(-3 + 2x + -4y) = 0 15 + 9x + 12y + (-3 * 2 + 2x * 2 + -4y * 2) = 0 15 + 9x + 12y + (-6 + 4x + -8y) = 0 Reorder the terms: 15 + -6 + 9x + 4x + 12y + -8y = 0 Combine like terms: 15 + -6 = 9 9 + 9x + 4x + 12y + -8y = 0 Combine like terms: 9x + 4x = 13x 9 + 13x + 12y + -8y = 0 Combine like terms: 12y + -8y = 4y 9 + 13x + 4y = 0 Solving 9 + 13x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + 13x + -9 + 4y = 0 + -9 Reorder the terms: 9 + -9 + 13x + 4y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + 13x + 4y = 0 + -9 13x + 4y = 0 + -9 Combine like terms: 0 + -9 = -9 13x + 4y = -9 Add '-4y' to each side of the equation. 13x + 4y + -4y = -9 + -4y Combine like terms: 4y + -4y = 0 13x + 0 = -9 + -4y 13x = -9 + -4y Divide each side by '13'. x = -0.6923076923 + -0.3076923077y Simplifying x = -0.6923076923 + -0.3076923077y
| 3x-2/4+x+57/7=13 | | 1.8z-1(-2+z)=1.5 | | 25x^2y^4-121= | | 4(5x-3)=68 | | 2=(x-2.7)/0.6 | | 25=-8x-87 | | 6/7=2n | | 11z+35=100 | | 2(x+3)=x+5 | | 3x=35+(-2y) | | 12/17+3/17= | | -7x+37=-3(1+5x) | | 7(8-3x)=182 | | 0.19y+0.07(y+4000)=1060 | | 5x-14=4(2x+1) | | x-4/3+4/3=-x/5 | | 2-3x=62 | | 8x^2+28x=-24 | | 8y-6=2y+8 | | 26/57=849/5x | | 5x/6-(3-x)/8=4x+3/12 | | 2xsquared+12.5=0 | | 1=2-3v+2v | | 33=-8x-31 | | 6(2w+v)-4(2v+1w)=0 | | -3/8p=-9 | | .6x^2=3.6x+.6 | | 5x+3=4x-14 | | 1/2(3t-7)=t/4+7/4 | | -(2x-5)-(2x-6)+3=-4(x-1)-(3x+5)+3 | | 6p+4p+.75+3p= | | -73+8x=71 |